2023
DOI: 10.3389/fpsyt.2023.1221694
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Atomoxetine improves chronic pain with comorbid post-traumatic stress disorder and attention deficit hyperactivity disorder

Satoshi Kasahara,
Miwako Takahashi,
Taito Morita
et al.

Abstract: BackgroundIt is known that patients reporting chronic pain often experience trauma or post-traumatic stress disorder (PTSD) and tend to be more difficult to treat. Attention deficit hyperactivity disorder (ADHD), a neurodevelopmental disorder, is frequently associated with chronic pain. Furthermore, patients diagnosed with ADHD are more likely to encounter trauma and develop PTSD because of their inattentive and impulsive tendencies. There are reports stating that atomoxetine (ATX), a selective noradrenaline r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…However, if ADHD occurs in a patient with ASD, medications for ADHD are available. Consistent with the findings in this case, studies have reported that ADHD medications can significantly improve chronic pain (25)(26)(27)(28)(29)(30)(31). It has also been reported that ADHD is more likely to be associated with chronic pain (32)(33)(34).…”
Section: Discussionsupporting
confidence: 88%
“…However, if ADHD occurs in a patient with ASD, medications for ADHD are available. Consistent with the findings in this case, studies have reported that ADHD medications can significantly improve chronic pain (25)(26)(27)(28)(29)(30)(31). It has also been reported that ADHD is more likely to be associated with chronic pain (32)(33)(34).…”
Section: Discussionsupporting
confidence: 88%